Preeclampsia subtypes: Clinical aspects regarding pathogenesis, signs, and management with special attention to diuretic administration. (July 2022) - Tamás, Péter; Kovács, Kálmán; Várnagy, Ákos; Farkas, Bálint; Alemu Wami, Girma; Bódis, József
Highlights: Preeclampsia is not a homogenous disease; subtypes are basically different in blood volume. In "classic" preeclampsia, thrombotic microangiopathy and vasoconstriction are responsible for organ damage and hypertension; the blood volume is low. In late maternal preeclampsia, extremely augmented water retention can explain all pathological events; obesity is a high risk factor. Different types of preeclampsia require different management strategies. Abstract: During normal pregnancy, blood volume increases by nearly two liters. Distinctively, the absence coupled with the extreme extent regarding the volume expansion, are likely accompanied with pathological conditions. Undoubtedly, preeclampsia, defined as the appearance of hypertension and organ deficiency, such as proteinuria during the second half of pregnancy, is not a homogenous disease. Clinically speaking, two main types of preeclampsia can be distinguished, in which a marked difference between them is vascular condition, and consequently, the blood volume. The "classic" preeclampsia, as a two-phase disease, described in the first, latent phase, in which, placenta development is diminished. Agents from this malperfused placenta generate a maternal disease, the second phase, in which endothelial damage leads to hypertension and organ damage due to vasoconstriction and thrombotic microangiopathy. In this hypovolemia-associated condition, decreasing platelet count, signs of hemolysis, renal and liver involvement are characteristic findings; proteinuria is marked and increasing. In the terminal phase, visible edema develops due to increasing capillary transparency, augmenting end-organ damages. "Classic" preeclampsia is a severe and quickly progressing condition with placental insufficiency and consequent fetal growth restriction and oligohydramnios. The outcome of this condition often leads to fetal hypoxia, eclampsia or placental abruption. The management is limited to a diligent prolongation of pregnancy to accomplish improved neonatal pulmonary function, careful diminishing high blood pressure, and delivery induction in due time. The other subtype, associated with relaxed vasculature and high cardiac output, is a maternal disease, in which obesity is an important risk factor since predisposes to enhanced water retention, hypertension, and a weakened endothelial dysfunction. Initially, enhanced water retention leads to lowered extremity edema, which oftentimes progresses to a generalized form and hypertension. In several cases, proteinuria appears most likely due to tissue edema. This condition already fully meets preeclampsia criteria. Laboratory alterations, including proteinuria, are modest and platelet count remains within the normal range. Fetal weight is also normal or frequently over average due to enhanced placental blood supply. It is very likely, further water retention leads to venous congestion, a parenchyma stasis, responsible for ascites, eclampsia, or placental abruption. During the management of this hypervolemia-associated preeclampsia, the administration of diuretic furosemide treatment seemingly offers promise.